Cultural Value in Income Accounting: The Case of Ilabulo Sellers in Indonesia - Thalib, Mohamad Anwar; Mamonto, Priciliana Natasya; Djeman, She Putri Chelonita (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2025)
Purpose: This study aims to explore the income accounting practices of Ilabulo sellers in Gorontalo, Indonesia, by emphasising the role of local wisdom in informal financial management. The research was motivated by the limited documentation of how traditional cultural values shape accounting behaviour among small informal businesses. It seeks to demonstrate how these values influence financial recording and decision-making processes. Method : To achieve this, a qualitative approach was employed using passive observation and structured interviews with selected Ilabulo sellers. These methods were used to gather insights into how income is tracked and how profits are allocated within their daily business practices. Findings: The findings reveal that income is not formally recorded but instead memorized, and profits are generally used for both personal needs and charitable giving. These practices reflect a strong adherence to the cultural value of diila o’onto, bo wolu-woluwo (invisible but present), which indicates the presence of spiritual values in financial decisions. The practical implication of these findings is the need to develop simple accounting systems that are in line with local cultural and spiritual values ​​to support informal business financial practices. Novelty: This study contributes to the accounting literature by revealing how spirituality and cultural wisdom are integrated into informal income accounting. It offers a culturally grounded perspective that challenges conventional assumptions in accounting.